Pengaruh Audit Internal, Whistleblowing System, dan Budaya Organisasi terhadap Pencegahan Kecurangan Dalam Pengelolaan Dana Desa di Kota Denpasar - Ni Luh Putu Suri Witari; Cokorda Gde Bayu Putra (UNHI Press, 2023)
Fraud prevention is very important to do in an institution, because fraud has become one of the problems that are quite often found in financial institutions. Fraud occurs in various institutions, one of which is the management of village funds which are full of opportunities for fraud. This study aims to determine the effect of internal audit, whistleblowing system, and organizational culture on fraud prevention. This research was conducted on the management of village funds in Denpasar City. The sampling technique used in this study was purposive sampling with a sample size of 81 village fund managers. The data were tested using multiple linear regression analysis. The results of the study indicate that internal audit has an effect on preventing fraud in the management of village funds in Denpasar City. Whistleblowing system affects the prevention of fraud in the management of village funds in Denpasar City. Organizational culture affects the prevention of fraud in the management of village funds in Denpasar City.